Transition from Laparotomy to Laparoscopic Repair of Congenital Duodenal Obstruction in Neonates: Our Early Experience - Cho, Min Jeng; Kim, Dae Yeon; Kim, Seong Chul; Namgoong, Jung Man (Frontiers in Pediatrics, 2017)
Background: The aim of this report was to review our early experience of the last 7 years with repairs of congenital duodenal obstruction (CDO) to determine the efficacy and outcomes of laparoscopic repairs compared to laparotomy. Methods: A retrospective review was conducted on all neonate (<30days) with CDO between 2009 and 2015. Patients with duodenal atresia, stenosis, web and annular pancreas were included. Patients with only malrotation or delayed presentation were excluded. Results: Twenty-six neonates underwent laparoscopy and 30 underwent traditional laparotomy. The operative time was longer in the laparoscopic group (P = .001), but time to initiation of feeds and time to full feeds were similar for the laparoscopic and open groups. There were no mortality, anastomosis leakage, or stenosis in the laparoscopic group. Six laparoscopic cases required conversion to an open procedure (23%). In the earlier cases, the open conversion rate was high, but it decreased over time (P = .003). Conclusions: Laparoscopic repair is safe and effective for repair of CDO in neonates. Despite operative time was slightly longer in the laparoscopic group, clinical outcomes remained similar to the open group. For pediatric surgeon with experience in laparoscopic techniques, laparoscopic duodenoduodenostomy is a sufficient available procedure.